Empowerment Model For Small Traders In Traditional Markets Through The Multi-Benefit Endorsement Program (Portal Iman) - Irawati, Diwi Acita; Astuti, Puji; Kurniawan, Wakhid; Herawati, Shabrina; Putra, Romi Iriandi; Ariyadi , Muhammad Yusuf (Green Publisher Indonesia, 2023)
The aim of this research was to find an effective empowerment model to alleviate traders from usury practices. A qualitative approach was employed through interviews, direct observations, social media observations, and literature studies. Traditional market locations were selected based on having more than 150 traders, and five markets were chosen: Bejen, Jungke, Nglano, Jaten, and Palur. The research results showed that usury practices burdened the traders significantly, but they had limited options for quick access to capital without complicated requirements. The presence of the Infaq Bank in eradicating usury practices has been beneficial to many business actors in Indonesia. In the Karanganyar region, the Infaq Bank named Bank Infaq Islamic Karanganyar has been operational for over 2 years. Seven study groups were formed for the empowerment of traders, with a total of 178 beneficiaries absorbing funds amounting to Rp. 278,000,000. The empowerment model for small traders in traditional markets through collaboration with the innovative Portal Iman received positive responses in five traditional markets, as evidenced by the willingness of worshippers, who are traders, to become permanent members of the Portal Iman study groups. This empowerment model involves four key roles: benefactors, motivators, managers, and beneficiaries of the Portal Iman. In conclusion, this empowerment model is acceptable for application among members of the Islamic Infaq Bank Karanganyar and the traditional market trader community in Karanganyar.